Association of clinical and laboratory parameters with ambulatory arterial stiffness index in acromegaly patients - Kilinc, Faruk; Pekkolay, Zafer; Demircan, Fatih; Gozel, Nevzat; Tuzcu, Alpaslan Kemal (Professional Medical Publications, 2018)
Objective: In this study, we determined the relationship between the ambulatory arterial stiffness index (AASI) and clinical and laboratory parameters in patients with acromegaly. Methods: Sixty-five patients with acromegaly, who visited to Dicle University Medical Faculty Department of Endocrinology (33 females and 32 males), were included in this study. The study control group consisted of 65 subjects. Demographic and clinical data were recorded. Laboratory data (complete blood count, blood urea nitrogen, creatinine, electrolytes, albumin, lipid profile, growth hormone [GH], insulin-like growth factor-1, and the 75-g oral glucose tolerance test) performed over the last year were evaluated. The AASI was obtained from 24-hour ambulatory blood pressure monitoring records of all patients. This study was completed in 15 months from 2013 to 2015. Results: Twelve patients (18.4%) had diabetes and 21 patients (32%) had hypertension. The mean AASI value was 0.41 +/- 0.14. The mean AASI value in the control group was 0.25 +/- 0.09. Growth hormone (GH) levels were positively correlated with the AASI values. AASI values tended to be higher in hypertensive subjects than that in normotensive individuals. Conclusions: Our results show that the AASI value increased in patients with acromegaly, independent of the increase in blood pressure. The AASI was strongly dependent on the degree of the GH increase in patients with acromegaly and may have an important role predicting cardiovascular risk in patients with acromegaly.
Keywords: Acromegaly; Ambulatory arterial stiffness index; Cardiovascular disease; Hypertension